Targeted DNA vaccines for enhanced induction of idiotype-specific B and T cells - Fredriksen, Agnete B.; Sandlie, Inger; Bogen, Bjarne (Frontiers in Oncology, 2012)
Background: Idiotopes (Id) are antigenic determinants localized in variable (V) regions of Ig. Id-specific T and B cells (antibodies) play a role in immunotherapy of Id+ tumors. However, vaccine strategies that enhance Id-specific responses are needed. Methods: Id+ single chain Fragment variable (scFv) from multiple myelomas and B cell lymphomas were prepared in a fusion format that bivalently target surface molecules on antigen presenting cells (APC). APC-specific targeting units were either scFv from APC-specific mAb (anti-MHCII, anti-CD40) or chemokines (MIP-1α, RANTES). Homodimeric Id-vaccines were injected intramuscularly or intradermally as plasmids in mice, combined with electroporation. Results: (i) Transfected cells secreted plasmid-encoded Id+ fusion proteins to extracellular fluid followed by binding of vaccine molecules to APC. (ii) Targeted vaccine molecules increased Id-specific B and T cell responses. (iii) Bivalency and xenogeneic sequences both contributed to enhanced responses. (iv) Targeted Id DNA vaccines induced tumor resistance against challenges with Id+ tumors. (v) Human MIP-1α targeting units enhanced Id-specific responses in mice, due to a cross reaction with murine chemokine receptors. Thus, targeted vaccines designed for humans can be quality tested in mice. (vi) Human Id+ scFv from 4 multiple myeloma patients were inserted into the vaccine format and were successfully tested in mice. (vii) Human MIP-1α vaccine proteins enhanced human T cell responses in vitro (viii) A hypothetical model for how the APC-targeted vaccine molecules enhance Id-specific T and B cells is presented. Conclusions: Targeted DNA Id-vaccines show promising results in preclinical studies, paving the way for testing in patients.